Peran Auditor Internal dalam Implementasi Manajemen Risiko pada Perguruan Tinggi - Retnoningrum Hidayah; Sukirman Sukirman; Dhini Suryandari; Rita Rahayu (Pusat P2M Politeknik Negeri Batam, 2018)
Implementation of risk management applies not only to companies but also to universities. However, the implementation of risk management to universities is still limited and still needs improvement. This limitation is due to the absence of special units in universities dealing with risk management issues. This article focuses on the implementation of risk management at Universitas Negeri Semarang by using descriptive analysis. The results show that Internal Control Unit on Unnes has run the IIA (2009) mandate related to its participation in the implementation of risk management system by sticking to independence and objectivity. Furthermore, the implementation of three line of defenses on Universitas Negeri Semarang has not been able to be implemented. This is due to the lack of resources in the field of risk management, as well as limited scope. Therefore, it is expected that the internal control unit able to always increase their role in developing, implementing and evaluating risk management system in universities.